1991
DOI: 10.1210/endo-129-6-3313
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Transforming Growth Factor-βProduction in Normal Human Osteoblast-Like Cells by 17β-Estradiol and Parathyroid Hormone

Abstract: Although our laboratory has reported that normal human osteoblast-like (hOB) cells contain estrogen receptors, we have failed to find major effects of 17 beta-estradiol (E2) on modulation of proliferation of bone matrix protein production by hOB cells. Because the major effect of E2 in vivo is to decrease bone resorption and because transforming growth factor-beta (TGF-beta) has been reported to decrease osteoclast-mediated bone resorption, we have tested the hypothesis that the effect of E2 on osteoclast acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
2
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(129 citation statements)
references
References 42 publications
(39 reference statements)
4
120
2
3
Order By: Relevance
“…Since exact figures on the cross-reactivity of the rat growth factors in our assays are unknown, it is possible that the correct absolute concentrations of these peptides may be different from the ones reported here. However (11)(12)(13)(14)(15) In the study presented here, we did not observe any increase in serum IGF-I during the course of the experiment. Based on the 95% confidence intervals of the IGF-I measurements, increases of > 10% should have been readily detected.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Since exact figures on the cross-reactivity of the rat growth factors in our assays are unknown, it is possible that the correct absolute concentrations of these peptides may be different from the ones reported here. However (11)(12)(13)(14)(15) In the study presented here, we did not observe any increase in serum IGF-I during the course of the experiment. Based on the 95% confidence intervals of the IGF-I measurements, increases of > 10% should have been readily detected.…”
Section: Resultsmentioning
confidence: 48%
“…The role of IGF-I as mediator of the anabolic effects of PTH on bone formation is additionally supported by findings that the stimulation of collagen synthesis in cultured rat calvariae after transient PTH administration can be suppressed by antibodies to IGF-I (13). PTH has also been reported to stimulate the secretion of IGF-II in mouse calvariae cultures ( 12, 14), whereas Oursler et al observed a dose-dependent stimulation of TGF-p-bioactivity and TGF-P3-message with PTH in cultures of human osteoblast-like cells (15).…”
Section: Introductionmentioning
confidence: 89%
“…TGFβ1 is present in the greatest abundance in bone [Seyedin et al, 1985]. This family of growth factors is known to be induced by estrogen in multiple cell types including human OBs [Oursler et al, 1991a] and OCs [Oursler et al, 1994]. In spite of their high sequence homology, the in vivo functions of the three TGFβ isoforms are highly divergent as analyzed by gene knockouts.…”
Section: Tgfβ Action In Ob Cellsmentioning
confidence: 99%
“…This increase in TGFβ production then acts on the surrounding OB cells to activate the TGFβ signaling pathway. In bone, E 2 induces TGFβ synthesis in several cell types including human OB cells [Oursler et al, 1991a;Hering et al, 1995;Slater et al, 1995;Hughes, 1998;Bord et al, 2001a], human bone marrow cells [Hong et al, 2004], as well as mouse and rat OB cells [Finkelman et al, 1992;Hughes et al, 1996;Narayana Murthy et al, 2006], mouse osteocytes [Heino et al, 2002], and even chicken OCs [Robinson et al, 1996]. In many of the above studies, the levels of TGFβ gene expression or protein were measured, while in other studies TGFβ activity was determined via activation of the R-Smads.…”
Section: Level 1 Cross-talk: E 2 Induction Of Tgfβ In Ob and Other Cementioning
confidence: 99%
See 1 more Smart Citation